(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the epidemiological aspects of dengue virus infection in pregnant women in the state of Pará, identifying the main factors that lead to the incidence of the disease in pregnant women. Methodology: This is a quantitative, retrospective, descriptive-exploratory study based on epidemiological data provided by the Unified Health System Informatics Department (DATASUS) from 2015 to 2019, in the integration regions of the State of Pará. 2,397 cases of dengue were identified in pregnant women during the period described with an increase in cases from 2015 to 2016, reductions between 2016 and 2018 and a new increase in the 2018 to 2019 cycle. Results and discussion: According to this research, in relation to the socio-demographic profile, the disease received more notifications in pregnant women who were in the second trimester of pregnancy, in the age group of 20 to 39 years and with respective cases in natives of the municipality of residence. There is a greater number of cases of the disease in the Health Regions of Carajás, Metropolitana I, Xingu, Araguaia and Rio Caetés. Final considerations: Dengue in pregnant women in Pará continues to exist as a neglected disease. For this reason, it demands the existence of actions aimed at preventing it among this public and at encouraging a greater understanding of the disease among the health professionals involved. More studies are needed to update the clinical-epidemiological data on dengue and their disorders.